The Effect of a Screening and Treatment Program for the Prevention of Fractures in Older Women: A Randomized Pragmatic Trial. (1st August 2019) - Merlijn, Thomas; Swart, Karin MA; van Schoor, Natasja M; Heymans, Martijn W; van der Zwaard, Babette C; van der Heijden, Amber A; Rutters, Femke; Lips, Paul; van der Horst, Henriëtte E; Niemeijer, Christy; Netelenbos, J Coen; Elders, Petra JM
ABSTRACT: Population screening for fracture risk may reduce the fracture incidence. In this randomized pragmatic trial, the SALT Osteoporosis Study (SOS), we studied whether screening for fracture risk and subsequent treatment in primary care can reduce fractures compared with usual care. A total of 11, 032 women aged 65 to 90 years with ≥1 clinical risk factor for fractures were individually randomized to screening ( n  = 5575) or usual care ( n  = 5457). Participants in the screening group underwent a screening program, including bone densitometry and vertebral fracture assessment. Participants with a high 10‐year fracture probability (FRAX) or a vertebral fracture were offered treatment with anti‐osteoporosis medication by their general practitioner. Incident fractures as reported by questionnaires were verified with medical records. Follow‐up was completed by 94% of the participants (mean follow‐up = 3.7 years). Of the 5575 participants in the screening group, 1417 (25.4%) had an indication for anti‐osteoporosis medication. Screening and subsequent treatment had no statistically significant effect on the primary outcome fracture (hazard ratio [HR] = 0.97; 95% confidence interval [CI] 0.87–1.08), nor on the secondary outcomes osteoporotic fractures (HR = 0.91; 95% CI 0.81–1.03), major osteoporotic fractures (HR = 0.91; 95% CI 0.80–1.04), hip fractures (HR = 0.91; 95% CI 0.71–1.15), falls (odds ratio [OR] = 0.91; 95% CI 0.72–1.15), or mortality (HR = 1.03; 95% CI 0.91–1.17). Post hoc explorative finding suggested that screening might be most effective after a recent fracture (HR = 0.65; 95% CI 0.44–0.96 for major osteoporotic fractures and HR = 0.38; 95% CI 0.18–0.79 for hip fractures). The results of this study might have been compromised by nonparticipation and medication nonadherence in the screening group. Overall, this study does not provide sufficient indications to consider screening for fracture prevention. However, we cannot exclude its clinical relevance to reduce (major) osteoporotic fractures and hip fractures because of the relatively small number of women with a treatment indication in the intervention group. © 2019 The Authors. Journal of Bone and Mineral Research Published by Wiley Periodicals, Inc.